Enhanced attitude control structure for small satellites with reaction wheels - Ismail, Zuliana (2019)
Attitude accuracies of a three-axis satellite are highly influenced by space environment disturbances and uncertainties. Similar to actuators, an attitude controller also plays an important role and must be robust enough to cope with any disturbances and uncertainties. Various controllers have been used for satellite attitude controls either linear or nonlinear control theories. This thesis presents an enhanced attitude control structure for a small satellite with reaction wheels (RWs) and the wheel angular momentum unloading control using magnetic torquers (MTQs). In order to improve the attitude control performances, a proportional derivative-active force control (PDAFC), and a Fuzzy PD-AFC are developed. For the momentum unloading control, a Fuzzy-proportional integral (Fuzzy-PI) is developed to remove the excess wheel momentum. Using the PD-AFC and Fuzzy PD-AFC, the actual disturbances torques are considered totally rejected by the system without having to have any direct prior knowledge on the actual disturbances itself. These days, however, satellites have become increasingly more complex, with many additional components, such as antennas, cameras, solar panels and mechanical manipulators. These components introduce flexible mode which results in a satellite dynamic system becoming highly nonlinear. Therefore, a robust nonlinear controller such as sliding mode control (SMC) is highly desirable. Besides, a number of studies have shown that, fractional order controller (FOC) could enhance the control system performance due to its extra degrees of freedom. In this thesis, a fractional order sliding mode control (FOSMC) is developed. In fact, this current work will be one of the maiden works on FOSMC for small satellites. All the proposed controllers were also tested for a satellite with only two functional RWs, in which the control allocation technique is proposed to solve the underactuated satellite attitude control problem. All the relevant attitude control architectures are developed together with their governing equations. Eventually, all control algorithms are numerically treated and analysed. The research results obtained proved that the PD-AFC, Fuzzy PD-AFC and FOSMC to be successful in achieving the overall stability attitude control system in the presence of external disturbances and uncertainties, i.e., PD-AFC (±0.0040° - 0.0055°) ; Fuzzy PD-AFC (±0.0010° - 0.0015°); FOSMC (±0.00020), and with the Fuzzy-PI for momentum unloading control whereby, the wheel momentum can be well maintained. Finally, the research for underactuated satellite attitude control performances using two RWs have been also successfully demonstrated and the research results proved that the control allocation technique provides a good performance in controlling the satellite attitude.